ANALISIS KAPASITAS RUANG PARKIR DI PUSKESMAS LASI KECAMATAN CANDUNG KABUPATEN AGAM - Nur Hidayat; Deddy Kurniawan; Surya Eka Priana (Ensiklopedia Research and Community Service Review, 2023)
Abstract : Parking facilities are an inseparable part of driving life. Parking facilities are quite a concern, especially when visiting places that are crowded with visitors such as public service centers, for example the Lasi Health Center. Puskesmas usually have a busy schedule of visitors at certain hours each day so that there are problems such as the absence of parking areas. To overcome this problem, it is necessary to identify the availability of parking areas at the Lasi Health Center by analyzing the characteristics and level of parking services at the Puskesmas, the analyzed characteristics such as parking volume, parking duration, parking accumulation, parking index, parking turnover rate, usage rate and parking capacity. From the results of research conducted for 6 days (11-16 July 2022) from 07.00-17.00 WIB and data processing, it can be concluded that: the largest incoming vehicles are 4 cars on Monday at 07.00 08.00 WIB and 24 motorcycles on Friday 07.00-08.00 WIB, the largest accumulation is 6 cars on Thursday and 19 motorbikes on Friday, the maximum parking duration is 2.6 hours for cars on Monday and the maximum parking duration is 3.01 hours for bicycles on Monday, the largest parking volume for cars is 12 vehicles on Wednesdays and motorbikes is 59 vehicles on Thursdays.Keywords: Parking Facilities, Availability of Parking Areas, Parking Characteristics, Parking Service Levels.